Analysis of acid resistance of 6,6'7-anhydroerythromycin D using FT-IRFT-IR spectrometric approach and microbial test - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
c16-7-Anhydroerythromycin D has been resulted from fermentation of Saccharopolyspora erythraea ATCC 11912 with additional isonicotinic hydrazide (INH) in order to produce an acidic resistant erythromycin derivative. The acid resistance analysis was carried out to the product, in series of pH, using FT-IR spectrometric approach and microbial test. The IR spectrogram showed the stability of the appearance of Câ-carbonyl group of the product under acidic condition (pH 3-5). This results were supported by the microbial tests.